Fortress of the Soul Violence, Metaphysics, and Material Life in the Huguenots' New World, 1517-1751 - Kamil, Neil (Johns Hopkins University Press, 2005)
French Huguenots made enormous contributions to the life and culture of colonial New York during the seventeenth and eighteenth centuries. Huguenot craftsmen were the city's most successful artisans, turning out unrivaled works of furniture which were distinguished by unique designs and arcane details. More than just decorative flourishes, however, the visual language employed by Huguenot artisans reflected a distinct belief system shaped during the religious wars of sixteenth-century France.In Fortress of the Soul, historian Neil Kamil traces the Huguenots' journey to New York from the Aunis-Saintonge region of southwestern France. There, in the sixteenth century, artisans had created a subterranean culture of clandestine workshops and meeting places inspired by the teachings of Bernard Palissy, a potter, alchemist, and philosopher who rejected the communal, militaristic ideology of the Huguenot majority which was centered in the walled city of La Rochelle. Palissy and his followers instead embraced a more fluid, portable, and discrete religious identity that encouraged members to practice their beliefs in secret while living safely-even prospering-as artisans in hostile communities. And when these artisans first fled France for England and Holland, then left Europe for America, they carried with them both their skills and their doctrine of artisanal security.Drawing on significant archival research and fresh interpretations of Huguenot material culture, Kamil offers an exhaustive and sophisticated study of the complex worldview of the Huguenot community. From the function of sacred violence and alchemy in the visual language of Huguenot artisans, to the impact among Protestants everywhere of the destruction of La Rochelle in 1628, to the ways in which New York's Huguenots interacted with each other and with other communities of religious dissenters and refugees, Fortress of the Soul brilliantly places American colonial history and material life firmly within the larger context of the early modern Atlantic world.